MicroRNA‐1 regulates chondrocyte phenotype by repressing histone deacetylase 4 during growth plate development. Issue 9 (23rd May 2014) - Li, Pengcui; Wei, Xiaochun; Guan, Yingjie; Chen, Qian; Zhao, Tingcun; Sun, Changqi; Wei, Lei
Abstract : MicroRNAs (miRs) are noncoding RNAs (17‐25 nt) that control translation and/or mRNA degradation. Using Northern blot analysis, we identified that miR‐1 is specifically expressed in growth plate cartilage in addition to muscle tissue, but not in brain, intestine, liver, or lung. We obtained the first evidence that miR‐1 is highly expressed in the hypertrophic zone of the growth plate, with an 8‐fold increase compared with the proliferation zone; this location coincides with the Ihh and Col X expression regions in vivo . MiR‐1 significantly induces chondrocyte proliferation and differentiation. We further identified histone deacetylase 4 (HDAC4) as a target of miR‐1. HDAC4 negatively regulates chondrocyte hypertrophy by inhibiting Runx2, a critical transcription factor for chondrocyte hypertrophy. MiR‐1 inhibits both endogenous HDAC4 protein by 2.2‐fold and the activity of a reporter gene bearing the 3'‐untranslated region (UTR) of HDAC4 by 3.3‐fold. Conversely, knockdown of endogenous miR‐1 relieves the repression of HDAC4. Deletion of the miR‐1 binding site in HDAC4 3'‐UTR or mutated miR‐1 abolishes miR‐1‐mediated inhibition of the reporter gene activity. Overexpression of HDAC4 reverses miR‐1 induction of chondrocyte differentiation markers Col X and Ihh. HDAC4 inhibits Runx2 promoter activity in a dosage‐dependent manner. Thus, miR‐1 plays an important role in the regulation of the chondrocyte phenotype during the growth plate development via direct targeting of HDAC4. —Li, P., Wei, X., Guan, Y., Chen, Q., Zhao, T., Sun, C., Wei, L. MicroRNA‐1 regulates chondrocyte phenotype by repressing histone deacetylase 4 during growth plate development. FASEB J. 28, 3930‐3941 (2014). www.fasebj.org